2010
DOI: 10.1007/bf03091750
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of ventricular tachyarrhythmia in high-risk myocardial infarction patients treated with primary coronary intervention

Abstract: Background. We investigated the association between clinical characteristics, angiographic data and ventricular arrhythmia in patients with ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI). Methods. In patients with STEMI (n=225), a Holter analysis was performed the first 12 hours after primary PCI.Results. A total of 151 (66%) patients had ≥1 episode of ventricular tachycardia (VT). Age <70 years (RR 4.9, 95% CI 1.8 to 12.7), TIMI 0-1 pre-PCI (RR 2.6, 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Ventricular tachycardia frequently complicates the clinical course of patients hospitalized with acute myocardial infarction and is associated with worse in-hospital and long-term outcomes, especially sudden cardiac death [ 1 , 2 ]. The development of ventricular tachycardia (VT) in patients with an acute myocardial infarction (AMI) is typically associated with a larger infarct, ST segment elevation, left ventricular dysfunction, and more extensive underlying coronary artery disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular tachycardia frequently complicates the clinical course of patients hospitalized with acute myocardial infarction and is associated with worse in-hospital and long-term outcomes, especially sudden cardiac death [ 1 , 2 ]. The development of ventricular tachycardia (VT) in patients with an acute myocardial infarction (AMI) is typically associated with a larger infarct, ST segment elevation, left ventricular dysfunction, and more extensive underlying coronary artery disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Literature reports that patients receiving thrombolytic therapy have an increased likelihood of developing VAs than patients that received reperfusion therapy via PCI [9]. Nonetheless, VAs can still occur during the acute phase of STEMI even with early and effective reperfusion therapy [15]. This illustrates that the QTc interval is an important risk factor of VAs in STEMI patients leading to an increased mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Most episodes of VT in STEMI patients occur within the fi rst 48 hours. Studies have shown that the main predictors for the occurrence of early VT in patients with STEMI are age, the absence of anterograde epicardial fl ow in the infarct artery before PCI and larger infarction zone [2]. Other studies suggest that low systolic blood pressure aft er primary PCI is the main predictor of early VT/ VF [2,14].…”
Section: Ventricular Tachycardiamentioning
confidence: 99%
“…Studies have shown that the main predictors for the occurrence of early VT in patients with STEMI are age, the absence of anterograde epicardial fl ow in the infarct artery before PCI and larger infarction zone [2]. Other studies suggest that low systolic blood pressure aft er primary PCI is the main predictor of early VT/ VF [2,14]. When the "sustained "VT occurs later in STEMI (over 24 hours), it is associated with increased mortality in the fi rst 30 days of follow-up compared with patients who did not have "sustained" VT [15].…”
Section: Ventricular Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation